전통공연예술 산업의 글로벌 경쟁력확보를 위한 전략적 방안 모색에 관한 연구 - 임영순(Young-Soon Lim); 맹해양(Hai-Yang Meng); 배기형(Ki-Hyung Bae) (한국콘텐츠학회 논문지, 16(4), 2016)
Traditional Performing Arts is a key element of national competitiveness that represents the identity of a country. Preserving traditional performing arts such as traditional culture overall aggregate such as literature, art, music, dance, theater and enable it to meet future national culture is to secure a competitive brand. Meanwhile, it shrouded in advance global success of K-pop and TV content, such as our popular culture, but our traditional performing arts sector, there has been a steady effort to receive the attention of the world and expanding capacity and performance. Now, this point will be a new policy approach needed to expand more popular in both domestic and world demand in traditional performing arts. In this study, we propose a strategic plan to raise the popularization and industrialization of our own needs and unique traditional performing arts opportunities for successful overseas expansion and promotion of the content of traditional performing arts.With the help of information technology. 전통공연예술은 한 국가의 정체성을 나타내는 국가경쟁력의 핵심요소로 많은 국가들은 자국의 독특한 전통공연예술 장르를 대중화, 산업화하는 등의 노력을 기울이고 있다. 전통예술은 문학, 미술, 음악, 무용, 연극 등 총체적인 집합체로 이러한 전통문화를 보존하고 미래의 문화에 부합하도록 활성화하는 것은 경쟁력 있는 국가브랜드를 확보하는 일이라고 볼 수 있다. 그동안 K-pop 및 드라마 등 우리 대중문화 콘텐츠의 세계적인 진출성공사례에 가려져 있지만 우리 전통공연예술분야는 꾸준한 역량 확대 및 세계의 주목을 받는 노력과 성과가 있어 왔다. 이제는 전통공연예술 분야에서 국내 및 세계에서 보다 대중적인 수요를 확대하기 위해 새로운 정책적 접근이 필요한 시점일 것이다. 따라서 본 연구에서는 전통공연예술 장르의 대중화, 산업화의 필요와 우리만의 독특한 전통공연예술 콘텐츠의 성공적인 해외 진출 및 진흥기회를 마련하기 위한 전략적 방안을 모색해 보고자 한다. 이를 위하여 먼저 전통공연예술의 개념을 정의하고 전통공연예술 산업의 현황을 정리하였다. 또한 이러한 전통공연예술 산업의 현황을 토대로 우리나라 전통공연예술 콘텐츠의 해외 시장 저변확대를 위한 전략적 방안을 제안하였다.